Peran Penyuluh Agama Buddha dalam Penguatan Moderasi Beragama - Marjianto . (Balai Diklat Keagamaan Semarang, 2026)
This study explores the challenges and strategies of Buddhist religious instructors in promoting religious moderation in Central Java. Using a phenomenological qualitative approach, data were collected through in-depth interviews, participatory observation, and questionnaires involving 62 active instructors. The findings reveal five main dimensions of challenges: humanitarian, religious, national, cultural, and digital. In response, instructors employ various strategies, including community-based outreach, interfaith dialogue, the use of social media, and the internalization of Middle Way values from Buddhist teachings. These findings are examined through the lens of religious moderation theories, highlighting the gap between theoretical frameworks and digital-age complexities. The study emphasizes the importance of institutional support and the integration of multicultural values into public policy. Its main contribution lies in proposing a contextual, inclusive, and adaptive model of religious moderation for pluralistic societies